49-2x=9-7x

Simple and best practice solution for 49-2x=9-7x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 49-2x=9-7x equation:


Simplifying
49 + -2x = 9 + -7x

Solving
49 + -2x = 9 + -7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '7x' to each side of the equation.
49 + -2x + 7x = 9 + -7x + 7x

Combine like terms: -2x + 7x = 5x
49 + 5x = 9 + -7x + 7x

Combine like terms: -7x + 7x = 0
49 + 5x = 9 + 0
49 + 5x = 9

Add '-49' to each side of the equation.
49 + -49 + 5x = 9 + -49

Combine like terms: 49 + -49 = 0
0 + 5x = 9 + -49
5x = 9 + -49

Combine like terms: 9 + -49 = -40
5x = -40

Divide each side by '5'.
x = -8

Simplifying
x = -8

See similar equations:

| 5a=2a+7 | | x=1.4-(1.2x) | | X+6.5=9.7 | | 5+3x=-2x | | -3+6v=3(3v+4) | | 4(5x+3)-5(2x+1)=27 | | 4x+9=40-3x | | 3(3x+1)=39 | | 6a=6a+7 | | -38-8x=-3(-6+5x) | | 4+12x=4+x | | 2x^2y+xy-100=0 | | 4+x=3x-2 | | 3.2+6=6m-15 | | 5m=8m-15 | | -(r-5-8p)= | | 4M+3M=12 | | 8(5+13x)-(-2x+8)=32 | | -7x+2.3=7x-7.9 | | -14-(-3)= | | -28+8x=4-6(2-2x) | | x^2+kx+(k+1)=0 | | 14(12k-12)+14(-10k-11)=42 | | -2.5x+18-1.6x=57 | | 30-4n=-(n-6) | | -2(2t+8)=-28 | | (4x-4)(3x-7)= | | -52=a-11 | | 14+(4p+46)+0= | | 5-(x+3)=6 | | 6[4+7(3-2)]= | | -52=-11 |

Equations solver categories